Treatment of industrial detergent wastewater via membrane separation - Bahrun, Mohd Shakir (2010)
This thesis presents the experimental study of the potential of Nanofiltration membrane in treating industrial detergent wastewater that contains high Linear Alkylbenzene Sulfonate (LAS).LAS is the most common synthetic anionic surfactant used in domestic and industrial detergents and can cause significant environmental problems.This study was focused on treated wastewater sample from FPG Oleochemical Sdb Bhd based on decreasing the parameters so it can comply with the regulation of Environment Quality Act(EQA),1974 before it can release to discharge.LAS,Chemical Oxygen Demand(COD), Total Organic Carbon (TOC),Total Suspended Solid(TSS) and Turbidity were used as a parameters used in this study. The Polyamide Nanofiltration membrane performance was characterized by varying the Trans Membrane Pressure(TMP)3, 4,5 and 6 bars.The results showed that the optimum operating condition of the Nanofiltration membrane was achieved at TMP 6 bar.The removal percentage of the parameters is high which is more than 88%.However,only the Turbidity and TSS has achieved the EQA regulation.It is concluded that the wastewater from the production of Dynamo in FPG Oleochemical Sdn Bhd can be fully treated by using Nanofiltration membrane in addition some pre treatment or furthertreatment.